Refined understanding of the impact of the Mycobacterium tuberculosis complex diversity on the intrinsic susceptibility to pretomanid - Rupasinghe, Praharshinie; Reenaers, Rabab; Vereecken, Jens; Mulders, Wim; Cogneau, Sari; Merker, Matthias; Niemann, Stefan; Vally Omar, Shaheed; Rigouts, Leen; Köser, Claudio U.; Decroo, Tom; de Jong, Bouke C. (Microbiology spectrum, 2024)
This study confirmed that the Mycobacterium tuberculosis complex lineage 1, responsible for 28% of global tuberculosis cases, is less susceptible to pretomanid (Pa). It also refined the understanding of the intrinsic susceptibilities of lineages 5 and 6, most frequent in West Africa, and lineages 8 and 9. Regulators must review whether these in vitro differences affect the clinical efficacy of the WHO-recommended BPaL(M) regimen and set breakpoints for antimicrobial susceptibility testing accordingly. Notably, regulators should provide detailed justifications for their decisions to facilitate public scrutiny.